KASHKAR RUBOBI INSTRUCTION TEACHING METHODS IN GRADES 5-7 MUSIC CLUBS - Kuldoshev Umidbek (Journals Park Publishing, 2022)
This in the article about the method of teaching the Kashgar rubab instrument in the lessons of music clubs for grades 5-7 complete information you get possible .
Keywords: 5-7 grades; rubobi instrument; teaching methodology